Pengungkapan Sustainability Report dan Nilai Perusahan: Studi Empiris di Indonesia dan Singapura - Tedy Kurniawan; Hafiez Sofyani; Evi Rahmawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
The categories of sustainability report disclosure consist of economic, environment, and social. This research aims to examine the influence of each categories of sustainability report disclosure on firm value. This research use secondary data from all companies that listed on Indonesia Stock Exchange and Singapore Stock Exchange in 2014-2016. There are 116 samples that obtained from purposive sampling method. The results of this research show that only economic category of sustainability report has positive influence on firm value in Indonesia and Singapore. The environment category of sustainability report has negative influence on firm value, while the social category doesn’t have influence on firm value. The result of this research indicate that sustainability report disclosure which reported appropriately with choosen standard, especially in economic category will be useful to increase firm value in the point of view of investors. Keywords: sustainability report, GRI-G4, firm value